The Potential of Men’s Sheds as a Resource for Men Coping with Mental Health Challenges and Addiction - Heinz, Melinda (South Eastern European Journal of Public Health (SEEJPH), 2022)
Men’s Sheds are defined as grassroots community-based organizations comprised of men coping with mental health challenges and addiction. Men in need experience the benefits of receiving support from other men and feel that their levels of loneliness and depression declined after they joined the Men’s Shed. Men’s Sheds could serve as a mental health refuge for a variety of men with diverse needs. It may be worthwhile to pilot a program investigating the efficacy of using Men’s Sheds to support individuals recovering from addictions. Conflicts of interest: None declared Source of funding: None declared